2004
DOI: 10.1111/j.1365-2249.2004.02637.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a population of small macrophages in induced sputum of patients with chronic obstructive pulmonary disease and healthy volunteers

Abstract: SUMMARYThe inflammatory process in chronic obstructive pulmonary disease (COPD) is active mainly in the airways, but little is known about the properties of the inflammatory cells in this compartment. We have studied leucocytes in induced sputum of COPD patients compared to controls in order to uncover what types of macrophages might be involved in the disease. Sputum induction was performed by inhalation of nebulized sodium chloride solution. Leucocytes were isolated and stained with specific monoclonal antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 37 publications
5
52
1
5
Order By: Relevance
“…Although not statistically significant, this may be indicative of active inflammation, and could (like eosinophils) be another indicator of inflammatory airway disease. Indeed, one study (28) has shown an increase in a population of small macrophages in another respiratory disorder, chronic obstructive pulmonary disease (COPD).…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, this may be indicative of active inflammation, and could (like eosinophils) be another indicator of inflammatory airway disease. Indeed, one study (28) has shown an increase in a population of small macrophages in another respiratory disorder, chronic obstructive pulmonary disease (COPD).…”
Section: Discussionmentioning
confidence: 99%
“…Since one of the main functions of macrophages in inflammation is to recruit additional leukocytes, we have studied expression of chemokines, and for this we screened for CCL chemokines that target CCR1-4 in a pilot study on up to five COPD patients (data not shown). Among these CCL 3,4,5,8,11,14,15,17,23,24 and 26 showed no expression, or the difference in expression level between COPD samples with high percentage of small macrophages and control samples with low percentages of small macrophages was less than three-fold (data not shown).…”
Section: Chemokine Gene Expression In Copd Sputum Macrophagesmentioning
confidence: 99%
“…Sputum induction and processing were carried out as described previously (8,9) with some modifications. Briefly, the subjects were asked to inhale sterile saline solutions from 0.9% up to 3% in COPD and to 5% in healthy controls.…”
Section: Sputum Induction and Processingmentioning
confidence: 99%
See 2 more Smart Citations